Perfil dos consumidores de produtos cárneos industrializados no município de Medianeira-PR - Sá, Luana Izaniele de (2016)
The aim of this study was to develop and apply a questionnaire related to the consumption of processed meat products. Thus, to evaluate the consumer information of these products in relation to its composition, the action of the salt in the human body and chronic diseases. The questionnaire was applied to a sample of300 consumers in two supermarkets and the campus of the Federal University of Technology in the city of Medianeira Paraná, Paraná state. A survey on the Bank Customer Service Data was conducted, in a meat packing company in the western Paraná, the Customer Service (SAC), as the complaints, questions and compliments about the processed meat products. Consumers had a mean age of 27 years and believe that salt reduction in processed foods may decrease the incidence of chronic non communicable diseases, such as hypertension. In the SAC calls, greater participation in the contacts of the categories of suggestions were males, with 61.5%of the total demand, as well as in the category of praise for processed meat products, with 56.5% of the total. The categories of claims and changes were made mostly by females, with percentages of 54.6% and 65.7% respectively. These calls were classified into subcategories, such as sensory changes, which accounted for 58% of contacts complaints and 64.2% in the category of trade, microbiological changes, was the sub-category which totaled 23.9% of complaint calls and 28.5% of the exchange of visits, and another subcategory with significant participation in the consultations was the presence of foreign bodies in the processed meat foods, which obtained a percentage of 32.4% in the category of claims and 24.7% in the category of trade . These data demonstrated that the majority of consumers have the perception that excessive consumption of processed foods can harm health but the frequency of consumption of them has not diminished. It was also observed that industrialized products which respondents consume more are among those who were the cause of most contact information, complaint and return the SAC calls. According to the data obtained, it is worth noting that companies should give a significant importance to the contacts made through the SAC calls, because it is through them that the degree of consumer satisfaction for the product that is offered is evaluated, after all these people are the reason for the existence of the organizations.